Green Technology Book: Solutions for Climate Change Adaptation - World Intellectual Property Organization (World Intellectual Property Organization, 2022)
The Green Technology Book puts innovation, technology and intellectual property at the forefront in the fight against climate change. This inaugural edition focuses on three important areas: agriculture and forestry, water and coastal regions, and cities, showcasing 200 available solutions that aim to reduce vulnerability and increase resilience to climate impacts.